THE INFLUENCE OF SHIFTWORK ON LIVER DYSFUNCTION OF WORKERS AT INALUM COMPANY KUALA ANJUNG, NORTH SUMATERA - Royman S Panjaitan; Sartini Sartini; Ida Fauziah (Universitas Negeri Medan, 2022)
This study was conducted to determine the effect of the shiftwork system on liver dysfunction workers characterized by elevated of liver function enzymes SGOT (Serum Glutamic Oxaloacetic Transaminase) and SGPT (Serum Glutamic Pyruvate Transaminase) in the employees at Inalum Company at Kuala Tanjung. The research was derived from primary and secondary data. Primary data was conducted by a direct examination of SGOT and SGPT enzymes at liver (expressed in Unit units per liter of blood serum (U/L). The secondary data obtained from the Smelter Public Relations. All data obtained were analyzed using paired t-test analysis techniques by comparing SGOT and SGPT enzymes between 324 shift and non-shift workers. Results showed significant differences in SGOT and SGPT among 162 employees with shift work from the average SGOT period I 34.4 U/L rise to 42.0 U/L in period II and the average SGPT at period I was 62.5 U/L to 73.4 U/L in period II. While the average SGOT and SGPT among 162 non-shift employees also increased, but still in normal limit (SGOT <35 U/L and SGPT <45 U/L). Employees with a shift work system experienced an elevated of SGOT and SGPT which resulted impact on liver dysfunction caused by fatigue and no resting time. Whereas non-shift employees experienced an elevated of SGOT and SGPT but have no affect liver dysfunction.